2017
DOI: 10.1177/0961203317713141
|View full text |Cite
|
Sign up to set email alerts
|

Anti-carbamylated protein antibodies in systemic lupus erythematosus patients with articular involvement

Abstract: Objective Several studies have evaluated the prevalence of rheumatoid factor (RF) and anti-citrullinated proteins antibodies (ACPA) in systemic lupus erythematosus (SLE) patients but no data are available on the anti-carbamylated proteins (anti-CarP), a new biomarker for rheumatoid arthritis (RA). We evaluated the anti-CarP prevalence in SLE patients with joint involvement and the associations with different phenotypes. Methods Seventy-eight SLE patients with joint involvement were enrolled (F/M 73/5; mean ± S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…This observation contrasts, however, with reports of high levels of anti-CarP Ab in rheumatic disorders, including RA [19,31,40,41], systemic lupus erythematosus (SLE) [42,43], and Sjögren’s syndrome [44]. In these studies, Ab levels associated with disease activity (in RA [19], SLE[42,43] and Sjögren's syndrome [44]) and with bone erosion (in RA [4547]), and were predictive of RA onset in anti-CCP-positive patients with arthralgia without arthritis [48]. The postulated mechanism underlying these findings is that anti-CarP Ab levels increase concomitantly to the increase in carbamylated protein triggered by inflammation caused by the disease [19,44].…”
Section: Discussioncontrasting
confidence: 63%
“…This observation contrasts, however, with reports of high levels of anti-CarP Ab in rheumatic disorders, including RA [19,31,40,41], systemic lupus erythematosus (SLE) [42,43], and Sjögren’s syndrome [44]. In these studies, Ab levels associated with disease activity (in RA [19], SLE[42,43] and Sjögren's syndrome [44]) and with bone erosion (in RA [4547]), and were predictive of RA onset in anti-CCP-positive patients with arthralgia without arthritis [48]. The postulated mechanism underlying these findings is that anti-CarP Ab levels increase concomitantly to the increase in carbamylated protein triggered by inflammation caused by the disease [19,44].…”
Section: Discussioncontrasting
confidence: 63%
“…We previously identified anti-CarP in 46.1% of patients with SLE with joint involvement, a prevalence matching that in patients with RA and significantly higher than that in healthy controls (2.4%). We also found that anti-CarP-positive patients were significantly more frequent than ACPA-positive patients [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paralleling ACPA behavior, anti-CarP could induce the production of pro-inflammatory cytokines, leading to a more active phenotype. Nonetheless, anti-CarP seem specifically involved in joint involvement development rather than being markers of disease activity, since they do not correlate with disease activity indices, such as the SLEDAI-2 k. We may hypothesize that NETosis-derived myeloperoxidase could locally determine a pro-carbamylation milieu, leading to the break of immune tolerance and to the production of antibodies directed against carbamylated proteins [ 20 ]. NETosis, the specific neutrophil death, plays a fundamental role in SLE pathogenesis: several data have shown increased NETosis in patients with SLE, which significantly correlated with disease activity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the association between anti-CarP antibodies and SLE has recently been assessed in large cohort studies of SLE patients with and without articular involvement; the findings showed a 50% prevalence of anti-CarP antibodies in SLE with joint involvement, which is higher than in patients without joint involvement [292]. A few recent studies have been considered with the anti-CarP antibodies and their significance in SLE with erosive phenotypes.…”
Section: Pathological Conditions Of Citrullinationmentioning
confidence: 99%